(untitled) (Journal of Oriental Studies, 2019)
The theme of women’s freedom in the literature of Egypt in the period after the conquest of inde- pendence. In the article features of the evolution of female images in prose works in the period after the conquest of independence are considered. And it is during this period that the problem of radical breaking of traditional forms of life, social reorganization of society, which require appropriate literary interpretation, arises with all its severity. Key words: Egyptian literature, modernism, Al-Khamisi, theme of women’s freedom in literature.